2001
DOI: 10.1385/ijgc:29:3:163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mast-Cell Stabilization in Cerulein-Induced Acute Pancreatitis in Rats

Abstract: It seems likely that mast cell activity may play an important role in the initiation and progression of acute pancreatitis. Ketotifen treatment may reduce the severity of AP in rats. The protective action of ketotifen in cerulein-induced acute pancreatitis is most probably owing to mast cell stabilization and stimulation of NO synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
14
0
4
Order By: Relevance
“…Mast cell activation in various experimental models of acute pancreatitis is well established [26], [36], [37]. Yonetci et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell activation in various experimental models of acute pancreatitis is well established [26], [36], [37]. Yonetci et.…”
Section: Discussionmentioning
confidence: 99%
“…al. showed that the mast cell stabilizing agent ketotifen attenuates cerulein-induced acute pancreatitis in rats [37]. Zhao et.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium cromoglycate and ketotifen have been shown to stabilize mast cells and prevent the increment in density of mast cells. 15,34,35 Thus, it may be suggested that hyperhomocysteinemiainduced cardiac hypertrophy may be associated with increase in density of mast cells and their degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…We respectfully disagree with the title of the letter by Dr Braganza since at this stage we believe that the role of mast cells, or haematin-activated mast cells, in pancreatitis remains poorly understood and possibly controversial, based on few published studies. For example, the mast cell stabilising compounds ketotifen5 and cromolyn6 had a protective effect in cerulein- and taurodeoxycholate-induced pancreatitis, respectively. In contrast, studies using mast-cell-deficient animals ( Ws/Ws rats that have a deletion in the c-kit gene) have not supported a key role for mast cells in experimental closed duodenal loop-induced acute pancreatitis 7.…”
mentioning
confidence: 99%